2010
DOI: 10.1088/0004-637x/711/2/1033
|View full text |Cite
|
Sign up to set email alerts
|

LoCuSS: A COMPARISON OF CLUSTER MASS MEASUREMENTS FROMXMM-NEWTONAND SUBARU—TESTING DEVIATION FROM HYDROSTATIC EQUILIBRIUM AND NON-THERMAL PRESSURE SUPPORT

Abstract: We compare X-ray hydrostatic and weak-lensing mass estimates for a sample of 12 clusters that have been observed with both XMM-Newton and Subaru. At an over-density of ∆ = 500, we obtain 1 − M X /M WL = 0.01 ± 0.07 for the whole sample. We also divided the sample into undisturbed and disturbed sub-samples based on quantitative X-ray morphologies using asymmetry and fluctuation parameters, obtaining 1 − M X /M WL = 0.09 ± 0.06 and −0.06 ± 0.12 for the undisturbed and disturbed clusters, respectively. In additio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
165
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(191 citation statements)
references
References 67 publications
24
165
1
1
Order By: Relevance
“…For the clusters we have in common, the ratio of X-ray masses measured at R 500 is M HE Zhang,500 /M HE 500 = 0.83 ± 0.13. This offset is similar to the offset we find between the X-ray and weak lensing masses discussed above, as expected since Zhang et al (2010) found M WL 500 ∼ M HE 500 . However for relaxed systems (four in total), we find good agreement between hydrostatic mass estimates, with a ratio of M HE Zhang,500 /M HE 500 = 1.00 ± 0.09.…”
Section: Figsupporting
confidence: 91%
See 4 more Smart Citations
“…For the clusters we have in common, the ratio of X-ray masses measured at R 500 is M HE Zhang,500 /M HE 500 = 0.83 ± 0.13. This offset is similar to the offset we find between the X-ray and weak lensing masses discussed above, as expected since Zhang et al (2010) found M WL 500 ∼ M HE 500 . However for relaxed systems (four in total), we find good agreement between hydrostatic mass estimates, with a ratio of M HE Zhang,500 /M HE 500 = 1.00 ± 0.09.…”
Section: Figsupporting
confidence: 91%
“…Such systems also show a clear tendency to have smaller weak lensing to X-ray mass ratios as a function of offset between the X-ray peak and the BCG position. On the other hand there is a mass normalisation offset for relaxed systems, but it is not significant, as found by previous studies (e.g., Vikhlinin et al 2009;Zhang et al 2010).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations